Assessing the Strategic Impact of Artificial Intelligence - Robotic Process Automation on Enterprise Architecture in the Telecommunications Industry - Umar, Abubakar; Abdulrazaq Imam, Isa; Ore-Ofe, Ajayi Ore-Ofe; Daniel Emmanuel, Dako; Sylvester Aondonenge, Dugguh; Abdulwahab Olugbenga , Lawal (Vokasi Unesa Bulletin of Engineering, Technology and Applied Science, 2024)
This project explores the strategic impact of Artificial Intelligence (AI)-enhanced Robotic Process Automation (RPA) on Enterprise Architecture (EA) within the telecommunications industry. Traditionally, RPA has been applied to automate repetitive tasks without altering underlying IT infrastructure, focusing primarily on operational efficiency. However, the integration of AI introduces cognitive capabilities to RPA, enabling more dynamic interactions within complex organizational systems. This project assesses how AI-driven RPA can influence EA by enhancing system efficiency, supporting business-IT alignment and promoting digital transformation. Through case studies and analyses of various telecommunications operations, the project investigates the dual role of AI-enhanced RPA in both streamlining enterprise-wide processes and maintaining adaptability to meet industry demands. The findings indicate that, while AI-RPA integration holds significant promise for accelerating operational improvements, it also presents unique challenges related to governance, scalability and long-term sustainability. This work contributes insights into the adoption of AI-driven RPA as a transformative tool for telecommunications, offering guidance on best practices for aligning automated systems with enterprise strategic goals.